Reviewing the psychological resilience levels of the students studying at the faculty of sports sciences in terms of different variables - Bas, Muhammet; Gundogdu, Cemal (Lahore Medical Research Center Llp, 2021)
Background: Resilience is a key psychological aspect of sport. Aim: The purpose of this study was to review the psychological resilience levels of the students studying at faculty of sports sciences in terms of different variables. Methods: The study was designed in general survey model. The study population was consisted of 670 participants who attended Mus Alparslan University Faculty of Sports Sciences whereas the study sample was consisted of 398 participants. Besides; 162 of the participants were female ((x) over bar age=21.3 +/- 1.9) and 236 were male ((x) over bar age=22.4 +/- 3.2). In the study; Brief Psychological Resilience Scale -developed by Smith et al., (2008) and adapted to Turkish by Dogan (2015)- was employed as data collection tool. To analyze the data; such descriptive statistical methods as t-Test and One-Way Analysis of Variance (ANOVA) were used. Results: It was identified that participants' psychological resilience scale scores differed statistically and significantly on behalf of male participants according to gender variable (p<0.05). Conclusion: In sum; participants' psychological resilience levels did not differ in terms of the variables of age, academic department, general average academic grades, mother's educational status, father's educational status and grade (class) but it differed on behalf of male participants according to gender variable.
Keywords: Physical education; psychological resilience; sports